Effect of Temporal Variation on Phoneme Identification Skills in 2-3 Year old Typically Developing Children (Article-2) - Powlin Arockia Catherine; Savithri S.R. (Journal of All India Institute of Speech and Hearing)
The present study investigated the ability of 2 to 3 year old Kannada speaking children to identify synthetic phonemes varying in voice onset time (VOT). Four picturable (two minimal pair) words with stop consonants contrasting in voicing (labial: /b/ and /p/, velar:/g/ and /k/) in word-initial position in Kannada were selected. These words as uttered by 21-year-old female native Kannada speaker were recorded and stored onto the computer memory. A VOT continuum from /b - p/, and /g - k/ were synthesized using Praat software which was audio recorded on to a CD. The edited tokens were audio presented to thirty (15 boys and 15 girls) 2 to 3 year old children individually. Subjects pointed to one of the pictures placed before them as they heard the tokens. The investigator noted their responses on a binary forced-choice scoring sheet. The results indicated that the 50% crossover from voiced to unvoiced cognate occurred in the lead VOT region and boundary width was wider for /g - k /continuum compared to /b - p/continuum. The results of the current study can be used to compare phoneme identification skills in clinical population of same age.